Namibia : Selected Development Impact of HIV/AIDS - World Bank (Washington, DC, 2013)
The report aims at providing an overview of selected, likely development impact of HIV/AIDS in the light of existing data. It was initiated as an exercise to assist policy makers in Namibia, in their effort to incorporate HIV/AIDS into the planning process on a regular basis. However, due to data limitations, the review at this stage does not provide detailed costing of the impact of HIV/AIDS on various sectors of the economy, thus, subsequent analysis should focus on detailed costing, and policy design alternatives. It analyzes the nature of the epidemic, and its likely impact, by examining the demographic consequences as a first step in making a comprehensive assessment, through spectrum models with comparative reference to the results generated by other studies. Conclusions imply that the primary impact of the epidemic could be in the reduction of life expectancy at birth, for although AIDS reduces the population growth, it does so in perverse ways, affecting the labor force in the form of skill shortages for the country. Moreover from the macroeconomic perspective, the epidemic is likely to affect the savings/investment relation, to the extent that the lack of skilled labor, and profitability in the private sector, will adversely impact economic growth. Responding to the epidemic requires ongoing public, donor, and private activities to mitigate its impact, and, suggestions include political will, societal openness to fight against the stigma, social policy reform to reduce vulnerability, and multi-sectoral action at various levels.